(untitled) (mathematica didactica, 2014)
In the present study we analysed students’ conceptions of zero in the special context of division by zero. The answers of 73 pupils of grade 7 in a German secondary school were analysed based on a filled in questionnaire. In order to categorize (mis-) conceptions of zero we recommend distinguishing between cardinal, operational, coding and rule-based views of zero. The coding view found in more than a quarter of the questionnaires is relatively frequent. Implications for teaching the subject are proposed as well as the use of the four aspects to classify passages of the literature concerning zero.